CHANGES IN THE CHEMICAL STRUCTURE OF THERMALLY TREATED WOOD - Tumen, Ibrahim; Aydemir, Deniz; Gunduz, Gokhan; Uner, Birol; Cetin, Hakan; Aydemir, Deniz (North Carolina State Univ Dept Wood & Paper Sci, 2010)
Changes in the chemical structure of hornbeam and uludag fir woods during thermal treatment were investigated at three temperatures (170, 190, and 210 degrees C) and three durations (4, 8, and 12 hours). After thermal treatment, the extents of degradation in the chemical structure of the samples were determined, and the effects on the chemical composition of hornbeam wood and uludag fir wood were investigated. The data obtained were analyzed using variance analysis, and Tukey's test was used to determine the changes in the chemical structure of uludag fir and hornbeam woods. The results showed that heating wood permanently changes several of its chemical structures and that the changes are mainly caused by thermal degradation of wood polymers. It was found that decreasing of the cellulose and holocelluloses ratio had a favorable effect on the interaction of the wood with moisture. According to the obtained results, hornbeam wood is affected more than uludag fir wood. For each wood, the maximum decreases of holocellulose and a-cellulose were found at 210 degrees C for 12 hours, and the maximum increase of lignin occurred at the same treatment combination.
Keywords: Uludag Fir Wood; Chemical Structure; Cellulose; Lignin; Solubility